(untitled) (MAUSAM, 1990)
It has been argued that centre of a well marked low pressure system (depression / cyclone) should theoretically move in the direction of vector (dn/dt). The initial point of the vector is at the centre of low pressure system from where the system moves to next position. Case studies on the depression of 3-8 July 1979 have stood the test of validity of this logic. While the direction of movement is dictated by the vector (dn/dt), the corresponding speed scalar, C, could although be reasoned out to be proportional to difference between vorticity tendencies at the consecutive positions, but the data used here do not support the reasoning.